Taking Flight Towards a Greener Future: Steps Airlines Can Take to Reduce Emissions - Kronold,Rabin; Nyström,Mikael (2023)
Background: For decades, aviation has been an important part of society and with its growth comes the increased environmental impact and the challenge to reduce this adversary effect and move towards sustainability. Objective: Find out how airlines can reduce their emissions and become more sustainable. Method: A literature review was conducted including scientific articles, data from Airbus and one airline to answer the problem definition. Results: Three pillars were identified in order to achieve the objective: efficient ground and aircraft operation, the use of sustainable aviation fuel, and advancement in aircraft and engine technology. Conclusion: While there are several challenges in establishing a sustainable airline, the adoption of sustainable aviation fuel at an accessible price is essential for a more significant impact on the environment. Today, the maximum blending ratio for sustainable aviation fuel stands up to 50 percent, but we need to reach 100 percent. In addition to technological advancement in fuel types, there are some prompt actions we can take today for an immediate effect and impact, such as efficient ground and aircraft operations. Alongside this, crew education and motivation are imperative to achieve fuel savings and emission reduction. However, an airline's financial stability and business model may impede their commitment to prioritizing sustainability measures.
Keywords: Sustainability; Aviation; Management; Emissions; Carbon footprint; Ground and aircraft operation; Fuel consumption; Contrails; Aircraft-Induced Clouds; Greenhouse gas emissions; Sustainable Aviation Fuel; FLYL01